Aethes hartmanniana - Budashkin, Yuriy; Richter, Ignác (Zenodo, 2021)
Aethes hartmanniana (Clerck, 1759) Material examined. 1♂, Montenegro. Tuzi, Cijevna river, 25.v.2010. Distribution. Europe, Russia (Kaliningrad region, Karelia, European Northwest region, European Northeast region, Central part of the European Russia, European south taiga region, Middle Volga, Volga–Don region, South Ural, South of Western Siberia, Krasnoyarsk region, Altai), Armenia, Asia Minor, Near East (Clerck 1759; Razowski 1970, 2002, 2009; Kuznetzov 1978; Sinev et al. 2019). : Published as part of Budashkin, Yuriy & Richter, Ignác, 2021, New records of Cochylini moths (Lepidoptera: Tortricidae) from the Balkans, pp. 441-456 in Zootaxa 5082 (5) on page 445, DOI: 10.11646/zootaxa.5082.5.3, http://zenodo.org/record/5796363 : {"references": ["Clerck, C. A. (1759) Icones Insectorum rariorum Cum Nominibus eorum trivialibus locisque e C. Linnaei Syst. nat. allegatis. Privately press, Holmiae [Stokholm], pls. 1 - 16.", "Razowski, J. (1970) Cochylidae. In: Amsel, H. G., Gregor, F. & Reisser, H. (Eds.), Microlepidoptera Palaearctica. 3 (Part 1 - Part 2). Georg Fromme & Co., Wien, pp. vii - xiv + 1 - 528 & pls. 1 - 161.", "Razowski, J. (2002) Tortricidae (Lepidoptera) of Europe. Vol. 1. Tortricinae and Chlidanotinae, F. Slamka Publ., Bratislava, 247 pp.", "Kuznetzov, V. I. (1978) 21 Sem. Tortricidae (Olethreutidae, Cochylidae) - listovjertki. In: Medvedev, G. S. (Ed.), Opredelitel' nasekomyh evropejskoj tchasti SSSR. 4 (1). Nauka (Leningradskoje otdelenie), Leningrad, pp. 193 - 710. [in Russian]", "Sinev, S. Yu., Nedoshivina, S. V. & Dubatolov, V. V. (2019) Tortricidae. In: Sinev, S. Yu. (Ed.), Catalogue of the Lepidoptera of Russia. 2 nd Edition. Zoological Institute RAS, St. Petersburg, pp. 120 - 156. [in Russian]"]}